2019
DOI: 10.1007/s10530-019-02052-3
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences for the management of different invasive alien forest taxa

Abstract: Invasive alien species (IAS) require management to mitigate their impact on ecosystems. The success of management decisions often depends on whether they are socially acceptable and to what extent people are willing to be actively involved in an early warning and rapid response system (EWRR). We administered a nationwide public poll to assess people's knowledge on plant, insect and fungal IAS; their perception of IAS as an environmental problem; and their support for different IAS management measures. Most res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 77 publications
6
10
0
Order By: Relevance
“…In any case, given the current pattern of invasion across the European oak forests for this species (Mutun et al 2009;Csepelényi et al 2017;Simov et al 2018;Tomescu et al 2018;Csóka et al 2019;Paulin et al 2020), the complete removal would now be impossible. In addition, in this study, women were more reluctant to support complete removal of OLB, which is in line with other studies (Fuller et al 2016;Japelj et al 2019). Furthermore, our research showed that the age of respondents also makes a difference.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…In any case, given the current pattern of invasion across the European oak forests for this species (Mutun et al 2009;Csepelényi et al 2017;Simov et al 2018;Tomescu et al 2018;Csóka et al 2019;Paulin et al 2020), the complete removal would now be impossible. In addition, in this study, women were more reluctant to support complete removal of OLB, which is in line with other studies (Fuller et al 2016;Japelj et al 2019). Furthermore, our research showed that the age of respondents also makes a difference.…”
supporting
confidence: 91%
“…However, in part, it is also likely due to the media interest that, in the last few years, has intensely covered the invasions in several cities in Europe where OLB is already established and damage is more visible, such as in Belgrade, Bucharest, Budapest and Zagreb. In addition, the estimation parameters in this study tended to confirm the hypothesis of a previous case study (Japelj et al 2019) that argued that women or more frequent visitors to the forest, were more likely to correctly recognise an IAS that was not easily visible.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Lethal options are the most common methods applied for successful eradication programs (Nogales et al, 2004) because they are considered more cost-effective than the in situ non-lethal option (Trap, Neuter, and Release [TNR]; Lohr et al, 2013). However, using lethal options for invasive species management often causes conservation conflicts, especially in residential areas (Japelj et al, 2019) because lethal options are not accepted by some citizens, particularly animal welfare stakeholders and cat owners (Lohr & Lepczyk, 2014;Mameno et al, 2017;. In particular, Japanese feral cat management has serious conservation conflicts because the rate of acceptance of the lethal option tends to be low among Japanese people.…”
Section: Introductionmentioning
confidence: 99%